(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
By increasing their electricity production capacity, this work focuses on a new wind farm configuration study currently in service. More specifically, a study that aims to enlarge the production area of the ventilated sites by implanting more wind turbines in optimal positions behind the existing turbines. In order to achieve this goal, we use Jensen’s linear wake pattern to describe the behavior of wind speed in wake, as well as a method based on the generation of a sequence of modified pseudo-random numbers as Mathematical approach to optimize the location of the wind turines. To perform numerical simulations, a program under MATLAB has been developed using the characteristics of the Gamessa G52 turbine and the data of the site in the production of Kaberten in Algeria. The results obtained from this study are presented and discussed.